A Applying Neuroscience Principles in a Tamansiswa-Aligned PBL Model to Enhance Fifth-Grade Students’ Learning Engagement: A Two-Cycle Classroom Action Research at SD Negeri 1 Depok, Kulon Progo, Yogyakarta - Heri Maria Zulfiati; Susan Chandra Mukti (JIPSINDO, 2026)
This study was motivated by the low level of student learning activeness despite the implementation of various learning models. The aim of this research was to enhance student engagement through the application of neuroscience theory in the Problem Based Learning (PBL) model integrated with the Tamansiswa philosophy. The study employed Classroom Action Research (CAR) conducted in two cycles. The research subjects were 26 fifth-grade students of SD Negeri 1 Depok, Kulon Progo. Data were collected using observation, questionnaires, interviews, and documentation, and analyzed through data reduction, display, and conclusion drawing. The findings revealed that the average student learning activeness increased from 55.22% in the first cycle (moderately active) to 77.20% in the second cycle (active). These results indicate that integrating neuroscience theory into PBL based on Tamansiswa’s philosophy effectively fosters active learning, enhances student self-confidence, and improves conceptual understanding.